Finite-frequency tomography using regional P-waves, with application to the western Pacific upper mantle - Totten, E (2021)
This thesis aims to present the data measurement process, waveform modelling, full waveform sensitivity measurements, and inversion workflow, required to produce a P-wave tomography of the upper mantle, including the mantle transition zone, down to 1000km depth.